Regulation of Ryanodine Receptor-Mediated Ca2+ Release in Vas Deferens Smooth Muscle Cells - Akitoshi Ohno; Susumu Ohya; Hisao Yamamura; Yuji Imaizumi (Elsevier, 2009)
Abstract.: Ca2+ release from intracellular store sites via the ryanodine receptor (RyR) and hormonal regulation by flutamide, an androgen-receptor (AR) antagonist, on it were examined in vas deferens (VD) smooth muscle cells (SMCs). VD and VDSMCs were obtained from two groups of male rats that were treated p.o. with 100 mg/kg flutamide (Flu) or vehicle (Vehicle). Both spontaneous and caffeine-induced Ca2+ releases were markedly smaller in single VDSMCs from Flu than in those from Vehicle. Interestingly, [Ca2+]i rise by 100 μM norepinephrine in VDSMCs from Flu was larger than that in those from Vehicle. The contractions induced by direct electrical stimulation in tissue preparations from Flu showed lower susceptibility to 30 μM ryanodine than those from Vehicle. Real-time PCR analyses revealed that the transcripts of ryanodine receptor (RyR) type 2 and type 3 (RyR2 and RyR3) were expressed in VD and markedly reduced in Flu. The protein expression of total RyR was significantly reduced by flutamide treatment, but that of inositol 1,4,5-trisphosphate receptor (IP3R) was not affected. It can be strongly suggested that long term block of AR by flutamide reduced the expression of RyR and its contribution to the contraction, but not those of IP3R in VDSMCs. Keywords:: ryanodine receptor, Ca2+ release, flutamide, vas deferens, smooth muscle